Liberalization and Risk-Taking: Evidence from Government-Controlled Banks - Illueca, Manuel; Norden, Lars; Udell, Gregory F. (Review of Finance, 2014)
Abstract We study the effects of the interplay between deregulation and governance on risk-taking in the financial industry. We consider the removal of regulatory geographic constraints for savings banks in Spain, the cajas, which led to a nationwide expansion of these banks during the past two decades. Based on a unique dataset that combines information on the geographic distribution of bank lending, matched lender-borrower financial statements, and borrower defaults, we find that the governance of the savings banks significantly affects the way in which they expand their lending activities. Savings banks that are subject to political influence by regional governments exhibit higher ex ante risk-taking and higher ex post loan defaults. Our study highlights the broader implications of the impact of global deregulation and consolidation and their interaction with governance issues.